Bile acids as biomarkers in carbonized archaeological sediment: Insights from dung burning experiments - Basira Mir-Makhamad; Thomas Larsen; Daniel Giddings Vassao; Robert Spengler; Yiming V. Wang (PLoS ONE, 2025)
Bile acids are increasingly used as fecal biomarkers for studying archeology, environmental pollution, paleoeconomy, and human-animal interactions. Exclusively synthesized by vertebrates, bile acids are more resistant to diagenetic degradation than other steroidal biomarkers. Although bile acids have been detected and analyzed in archaeological sediments, particularly in contexts where dung may have been used as fuel, their preservation after burning is poorly understood. In this study, we conducted controlled experiments on modern cattle dung to investigate the tolerance of bile acid to high temperatures (125°C, 233°C, 341°C, and 449°C). Bile acids were quantified before and after burning via High-Performance Liquid Chromatography coupled with Electrospray Ionization-Mass Spectrometry (HPLC-EI-MS). Our results indicate that elevated temperatures destabilize most bile acids to varying degrees. Primary and secondary bile acids showed moderate heat tolerance, persisting at reduced concentrations after exposure to the maximum furnace and open-air temperatures. In contrast, oxo-bile acids exhibited lower thermal stability and disappeared at exposure above 233°C. Open-air fires led to more significant overall bile acid loss than the furnace conditions, likely due to the higher temperatures. However, incompletely burned dung fragments from the cooler periphery of the fire pits, retained higher bile acid concentrations than fully combusted ashes. Our findings suggest that high temperatures complicate the use of bile acid profiles to distinguish species of origin. These persistent bile acids can, in archaeological contexts, provide valuable insights into past resource utilization, seasonal fuel use, mobility patterns, and environmental reconstruction.